Answer:
(k/Df)-b = t
t=(k/Df)-b
Step-by-step explanation:
D = k/f(b+t)
k/D = f(b+t)
k/Df = b+t
(k/Df)-b = t
24 students forget their pencil out of 120 students.
Exponential growth is the function
Exponential decay is the function
So, the basic difference is that in growth the base is more than 1, and in decay the base is more than 0 but less than 1.
Answer:
-49
Step-by-step explanation:
it would be this because first we would have to figure out what 6*10 is that why we know what to distribute . so once we figure it out , which is 70 . We would then subtract 14 from 70 . Since 7 is right next to 2 we would then multiply it to get to 14. Once we get that you should get 56, from there you would subtract 56 to 105 , and get your answer.